2021
DOI: 10.3390/ani11113111
|View full text |Cite
|
Sign up to set email alerts
|

Combining Grape Byproducts to Maximise Biological Activity of Polyphenols in Chickens

Abstract: Grape seeds (GS) and grape skins (GK) are natural sources of polyphenols with antioxidant capacity. An experiment was conducted to investigate in chickens the effect of including GS and GK (40 g/kg), individually or combined in different proportions (20 g/kg GS–20 g/kg GK; 30 g/kg GS–10 g/kg GK; 10 g/kg GS–30 g/kg GK), in a corn-soybean diet on growth performance, ileal and excreta contents of total extractable polyphenols (TEP) and tannins, ileal digestibility of protein, plasma and meat α-tocopherol concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Indeed, phenolic compounds originating from grape (mainly, catechins and proanthocyanidins) have shown to possess the capacity to scavenge free radicals and terminate oxidative reactions [20]. In this sense, several studies [21][22][23][24] have reported that the dietary inclusion of grape by-products (grape pomace, grape seeds and grape skins) has been effective in reducing lipid oxidation in the meat of broiler chickens, but there is a dearth of works evaluating the effect of dietary inclusion of grape products on yolk lipid oxidation [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, phenolic compounds originating from grape (mainly, catechins and proanthocyanidins) have shown to possess the capacity to scavenge free radicals and terminate oxidative reactions [20]. In this sense, several studies [21][22][23][24] have reported that the dietary inclusion of grape by-products (grape pomace, grape seeds and grape skins) has been effective in reducing lipid oxidation in the meat of broiler chickens, but there is a dearth of works evaluating the effect of dietary inclusion of grape products on yolk lipid oxidation [25].…”
Section: Introductionmentioning
confidence: 99%
“…The few research works existing on this topic have considered dietary doses of grape pomace ranging from 20 to 60 g/kg [25,29] and doses of grape seeds from 5 to 30 g/kg [30,31]. Previous studies in chickens have highlighted the importance of the grape source [23,24], since it has been demonstrated that the antioxidant potential of grape polyphenols and their effect on productive performance depend not only on their dietary dose but also on the polyphenol source. Depending on the grape products included in the diet, the same dietary dose of grape polyphenols may be detrimental for birds' productive performance or not.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of grape seeds at 2% into broiler’s diet for 5 wk also increased PUFA (13.4%), mostly n -3 PUFA (10.0%), and reduced SFA and MUFA amounts [ 85 ], as happened with grape pomace [ 80 ]. Furthermore, Romero et al [ 12 ] observed that the combination of grape seed and grape skins in broiler chickens’ diet resulted in lower meat lipid oxidation than the diets including grape seeds or grape skins separately. Thus, the antioxidant potential effectiveness of grape by-products depends on the nature and the total polyphenol content incorporated into the diet.…”
Section: Effects Of Dietary Grape By-products On Poultry Meat Quality...mentioning
confidence: 99%
“…Grape pomace, the major by-product of the grape industry, is a solid organic waste residue obtained after the juice extraction from grapes, consisting of pressed grape pulp and skins, as well as grape seeds and stems. It is estimated that around 20–25% of the total weight of grapes crushed for wine production results in grape pomace [ 11 , 12 ]. Grape stems, although least applied, are removed before winemaking and represent around 5% of wine by-products [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spain holds a significant position in the international wine economy, leading to a substantial availability of these grape by-products, which have the potential to be used as ingredients in animal nutrition [2]. In recent years, some authors have demonstrated the antioxidant capacity of these by-products in poultry [3,4], their prebiotic effect [5], as well as their potential to improve meat quality [6,7]. Furthermore, the identification of phenolic metabolites in the intestinal content and plasma of chickens that had consumed grape by-products [8,9] suggests that these compounds could be transferred to tissues where they may exert their antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%